2022
DOI: 10.1039/d2ta03412c
|View full text |Cite
|
Sign up to set email alerts
|

Thermally enhanced piezoelectricityviathe superstructure in Ca2Nb2O7single-crystals with ultra-high Curie temperature

Abstract: As the requirement of sustainable development and widen application range, it is very necessary to develop lead-free eco-friendly piezoelectric materials with ultra-high Curie temperature (Tc). The perovskite-like layered structure (PLS)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The peaks centered at approximately 529.5 eV (A) are attributed to crystal lattice oxygen, while the other peaks at high binding energy are assigned to oxygen vacancies and surface defects. [14][15][16][17] After Li/Ce dual doping, a notable shift can be found that the proportion of A increases and the proportion of B decreases, indicating that the doping leads to a reduction in the concentration of oxygen vacancies. This phenomenon is probably attributed to the formation of a denser surface following Li/Ce doping.…”
Section: Crystal Structure and Micromorphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks centered at approximately 529.5 eV (A) are attributed to crystal lattice oxygen, while the other peaks at high binding energy are assigned to oxygen vacancies and surface defects. [14][15][16][17] After Li/Ce dual doping, a notable shift can be found that the proportion of A increases and the proportion of B decreases, indicating that the doping leads to a reduction in the concentration of oxygen vacancies. This phenomenon is probably attributed to the formation of a denser surface following Li/Ce doping.…”
Section: Crystal Structure and Micromorphologymentioning
confidence: 99%
“…This observation indicates that the introduction of Li/Ce disrupts the local homogeneity, resulting in heightened disorder in the vibrations of La-O bonds, as La elements are replaced by Li/Ce.Fig.3(a) and (e) show the X-ray photoelectron spectroscopy (XPS) spectrum for the O 1s state. The peaks centered at approximately 529.5 eV (A) are attributed to crystal lattice oxygen, while the other peaks at high binding energy are assigned to oxygen vacancies and surface defects [14][15][16][17]. After Li/Ce dual doping, a notable shift can be found that the proportion of A increases and the proportion of B decreases, indicating that the doping leads to a reduction in the concentration of oxygen vacancies.…”
mentioning
confidence: 99%
“…Calcium pyroniobate (Ca 2 Nb 2 O 7 ) is a kind of potential alternative materials of piezoelectric ceramics due to its non-toxic and high-temperature stability properties. [1] The Ca 2 Nb 2 O 7 , with ultra-high Curie temperatures (Tc), possesses good stability performance when the temperature is over 1673 K. [2,3] Ca 2 Nb 2 O 7 also presents an excellent piezoelectric coefficient and electromechanical coupling coefficient. [1,[4][5][6] Besides, Ca 2 Nb 2 O 7 has been applied in the catalysts field, immobilization of nuclear waste field.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[4][5][6] Besides, Ca 2 Nb 2 O 7 has been applied in the catalysts field, immobilization of nuclear waste field. [1,2,[6][7][8][9][10] In recent years, although Ca 2 Nb 2 O 7 as leadfree piezoelectric material have been studied for different fields, but the investigation of isothermal and non-isothermal growth behaviors of Ca 2 Nb 2 O 7 in the molten slag is infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…The radius of cations in A2B2O7 composition family has three structural domination: fluorite (rA/rB < 1.48), pyrochlore (1.48 < rA/rB <1.78) and perovskite-like layered (PL) (rA/rB > 1.78) structure. Here Ln 3+ is A site cation and Ti 4+ is B site cation and these structures are complex (Gao et al, 2017;2013;Wang et al, 2010;2022;López-Pérez & Íñiguez, 2011;Hwang et al, 2003;Yamamoto et al, 1980;Nanamatsu et al, 1974). As a member of AnBnO3n+2 (n=4) family Ln-Ti-O (Ln =La, Nd, Pr) ternary systems are possess only PL structure (Sivagnanapalani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%